Evaluacion de los factores de mortalidad en la produccion del area semillera de san Juan Tetla, Puebla - Arceo Valenzuela, R.E.=700 1 Cibrian Tovar, D.
(Es, En)
Ilus., 7 ref.
Keywords: PINUS MONTEZUMAE; MORTALIDAD; PLAGAS DE PLANTAS; INSECTA; CECIDOMYIIDAE; DIPTERA; CYDIA; MEGASTIGMUS; DIORYCTRIA; CANOPTORUS PONDEROSAE; INSECTOS DEPREDADORES DE LAS FLORES; CONOS; MEXICO; REVISTA CHAPINGO